Fatal heart disease in patients with bone and soft tissue sarcoma - Chen, Bei; Zhao, Xin; Li, Xiying; Liu, Jun; Tang, Juyu (Frontiers in Cardiovascular Medicine, 2022)
Background/purpose: With improved cancer survivorship, non-cancer events, especially heart disease (HD), have become the underlying cause of death in cancer patients, but the risk of HD mortality in sarcoma patients remains poorly characterized. Therefore, our purpose was to: (1) identify sarcoma patients at the highest risk of fatal HD compared with the general population, (2) identify characteristics associated with a higher risk of HD death, and (3) determine if chemotherapy increased the risk of HD death in sarcoma patients. Methods: From 1975 to 2016, we identified patients diagnosed with bone and soft tissue sarcoma from the Surveillance, Epidemiology, and End Results (SEER) database in the US. Standardized mortality ratios (SMRs) were evaluated using mortality data from the general population collected by the National Center for Health Statistics. Results : In 80,905 sarcoma patients observed for 530,290 person-years, 3,350 deaths from HD were identified with a mortality of 631.7/100,000 person-years. The SMR of death from HD was 1.38 (95% CI: 1.33–1.42). The highest risks of death from HD were observed in patients with Ewing sarcoma (SMR = 5.44; 95% CI: 3.38–8.75) and osteosarcoma (SMR = 1.92; 95% CI: 1.55–2.38). Patients < 19 years of age had the highest SMR in all age subgroups (SMR = 9.46; 95% CI: 6.76–13.24), and HD plurality occurred in those with Ewing sarcoma (29.4%) and osteosarcoma (32.4%). The HD mortality risks were highest within the first year after diagnosis (SMR = 1.31; 95% CI: 1.21–1.41), and this risk remained elevated throughout follow-up. Subgroup analyses indicated that chemotherapy significantly increased the risk of fatal HD in patients with localized osteosarcoma (Hazard ratio (HR) = 3.18; 95% CI: 1.24–8.13; P = 0.016), but not in patients with other histological sarcoma subtypes and clinical stages. Conclusions The risk of death from HD mainly varied in patients with different histological sarcoma subtypes and clinical stages. Chemotherapy increased the risk of fatal HD in patients with localized osteosarcoma. To lower the risk of fatal HD in patients with sarcoma, we call for enhanced multidisciplinary cooperation, including cardiologists and orthopedic surgeons.